UTMD Suppresses CSF ‐1 to Drive Macrophage‐Mediated Ferroptosis in Papillary Thyroid Carcinoma - Yanqiang Niu; Zhenqiang Yao; Minghua Zhang; Jiayan Zhang; Yushan Li; Jinhui Xie; Zubang Zhou (Cancer Medicine, 2026)
ABSTRACT The tumor microenvironment (TME) of Papillary Thyroid Carcinoma (PTC), particularly the role of tumor‐associated macrophages (TAMs), contributes to therapeutic resistance. This study investigated whether ultrasound‐targeted microbubble destruction (UTMD), a non‐invasive physical modality, could reprogram the TME through modulation of TAMs and induction of ferroptosis. Transcriptomic profiling identified CSF‐1 as a top target suppressed by UTMD, which was validated by ELISA, Western blot, and qRT‐PCR. UTMD time‐dependently inhibited CSF‐1 expression and secretion, consequently attenuating PTC‐induced M2 macrophage polarization as evidenced by decreased CD206 + cells and M2 marker expression. Exogenous CSF‐1 rescued this effect, confirming the specificity of the mechanism. Functionally, M1 macrophages selectively induced ferroptotic death in PTC cells, whereas M2 macrophages promoted viability and ferroptosis resistance via GPX4 upregulation and suppression of lipid peroxidation. Critically, UTMD overcame M2‐mediated protection by downregulating CSF‐1, thereby sensitizing PTC cells to ferroptosis both in vitro and in vivo. In a subcutaneous xenograft model, UTMD significantly inhibited tumor growth, reduced intratumoral CSF‐1 and M2‐TAMs, increased M1‐TAMs, and triggered ferroptosis hallmarks including mitochondrial shrinkage and GPX4 downregulation. These findings establish that UTMD suppresses PTC‐derived CSF‐1 to drive TAM repolarization from M2 to M1, consequently sensitizing tumor cells to ferroptosis. This dual reprogramming of immune and metabolic TMEs positions UTMD as a promising non‐pharmacological strategy for refractory PTC.